Keabsahan Akta Jual Beli sebagai Akta Autentik yang Dibuat oleh Notaris dengan Adanya Penyalahgunaan Keadaan (Misbruik Van Omstandigheden) - Cintya Glady Amanda; Amanda Adellia Desty; Sherren Laurencia (CV Rewang Rencang, 2025)
This study examines the aspect of abuse of circumstances in making authentic deeds by Notaries in Decision Number 214/Pdt.G/2014/PN.Jkt.Sel. This study provides an understanding of the legal framework needed to protect vulnerable parties in contract agreements and suggests steps to prevent similar incidents in the future. This study uses a normative legal method. The conclusion is that the deed of sale and purchase made by a Notary with abuse of circumstances is considered invalid, and the injured parties can file a lawsuit with the District Court to file for cancellation of the deed of sale and purchase. When forming an authentic deed, it should be ensured in advance regarding the background of the sale and purchase relationship and its object.